Understanding Chinese language teachers' beliefs about themselves and their students in an English context. (February 2019) - Yang, Juan
Abstract: This study explores secondary Chinese language teachers' beliefs about themselves and their students in the UK. A qualitative approach with semistructured interviews is adopted to seek insights from nine secondary school teachers. The result shows that Chinese language teachers stress the importance of professional competency in terms of linguistic skills, content and pedagogical knowledge. Both native Chinese teachers and teachers of other language origin tend to have a student-centred teaching orientation. Nevertheless, cultural differences and challenges in adopting creative teaching approaches are noted by some novice teachers and teachers with Chinese educational experiences. In addition, teachers' beliefs about students' learning preferences and motivations indicate a deep understanding of their students' difficulties with and interests in learning Chinese characters. Implications for teacher professional development and teaching Chinese in cross-cultural settings are offered.